FINANCIAL ACCOUNTING INFORMATION AS AN AID IN MANAGEMENT DECISION MAKING OF FIRST BANK NIGERIA PLC - EGU USANG INAH; AGIM DAVID AGIABEKONG; JUAN ULOMA AMAEFULE (International Studies Journal)
Institutions and organizations have the responsibility of disclosing issues regarding their operations so as to aid managers in making decisions since management decision makers depend and count on information gained from financial accounting information to forecast future rates of return. There will always be a problem of how to determine the profit of a company, and evaluation of performance of a company without. This study therefore investigates the financial accounting information as an aid to management decision making of first bank Nigeria PLC. The general objective is to ascertain the role of financial accounting information on management decision making. To achieve the objective of this research work, A correlational survey research design was employed for the study and purposive and accidental sampling technique was used to obtain a sample of 400 First bank staff in South-South Geographical Zone of Nigeria. Data for analysis was collected using instrument designed by the researchers. The reliability coefficient value of sub-scales of the instruments range from .78 to .85. The research hypotheses were subsequently tested using Pearson Product Moment Correlation at .05 level of Significance. We discovered from the test of hypotheses that financial accounting information was relied upon in management decision making and financial accounting information is useful for forecasting company's performance. Conclusions were drawn based on the findings that financial accounting information plays a vital role on management decision making and it was recommended that no management decision should be taken without the consideration of a company’s financial accounting information.